Hierarchical structure and properties of high‐density polyethylene (HDPE) microporous films fabricated via thermally‐induced phase separation (TIPS): Effect of presence of ultra‐high molecular weight polyethylene (UHMWPE). (21st June 2022) - Yang, Bin; Wang, Shun; Ding, Mengya; Wang, Chengjun; Lv, Cheng; Wang, Yang; Yang, Yuqing; Zhang, Nuo; Shi, Zhiqiang; Qian, Jiasheng; Xia, Ru; Fang, Yirong
Abstract: In this study, HDPE/UHMWPE microporous films were prepared by blending UHMWPE and HDPE with DOP as the diluent via thermally‐induced phase separation (TIPS) method. Morphological studies showed that the phase separation mode of the mixed systems was hardly changed in the presence of UHMWPE. Both average pore size and porosity of the blend films increased firstly and then decreased with increasing UHMWPE content. When UHMWPE content reached 1.5 wt%, both porosity and average pore size of the film reached their maximum values (with a porosity of 84.8% and an average pore size of 0.79 μm). The addition of UHMWPE was found to not only enhance the thermal stability of the HDPE/UHMWPE blend films, but also greatly reduce their thermal shrinkage rate as well as the closed cell temperature, which made the diaphragms containing UHMWPE have good prospect for the application in lithium‐ion batteries (LIBs).